COACHES’ PERCEPTION OF VALUES EDUCATION: A SAMPLE OF ELAZIĞ - Bingölbalı, Abdullah; Yavuz, Cumaali; Karakaya, Yunus Emre (My University, 2021)
The aim of this study is to determine perceptions of coaches, who served in sports clubsin the city of Elazığ, toward values education. The sample group of the study consistedof 44 coaches who worked in sports clubs in the city of Elazığ. The data that were obtainedin the study were analyzed by using SPSS 22.0 package software. As a result of theanalyses, it was determined that the coaches in the study had the highest scores in the item“Values education is important for the future of our children” with 4.77 while the lowestscore was in the item “It is not necessary for coaches to include studies related to valueseducation in exercises” with 1.97. In certain items, statistically significant differenceswere observed in independent variables (Gender, Status of participating incourses/seminars related to values education, and Educational status). In conclusion, coaches and sports trainers have the privilege of contacting athletes easily. Therefore,they can emerge as the most effective individuals in terms of values education. In theinteraction process between athletes and coaches, content that is related to valueseducation can be included in coaching programs.
Keywords: Eğitim; Eğitim Araştırmaları; Spor Bilimleri